2022
DOI: 10.1002/ctm2.978
|View full text |Cite
|
Sign up to set email alerts
|

The driver role of JAK‐STAT signalling in cancer stemness capabilities leading to new therapeutic strategies for therapy‐ and castration‐resistant prostate cancer

Abstract: Background Lineage plasticity in prostate cancer (PCa) has emerged as an important mechanism leading to the onset of therapy‐ and castration‐resistant PCa (t‐CRPC), which is closely associated with cancer stem cell (CSC) activity. This study is to identify critical driver(s) with mechanism of action and explore new targeting strategy. Methods Various PCa cell lines with different genetic manipulations were subjected to in vitro prostasphere assay, cell viability assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
(82 reference statements)
0
6
1
Order By: Relevance
“…On the other hand, inhibitors of WNT/b-catenin (XAV-939), AKT (Capiversatib), HDAC (Panobinostat) and proteosome/NFkB (Bortezomib) all demonstrated an inhibitory effect or trend on prostate regeneration (Figure 6J), implicating these pathways in driving L1 generation and L1 regenerative activities. We also find JAK/STAT, which has received a lot of attention recently in relation to advanced PCa lineage plasticity [78][79][80] , to be one of the pathways deregulated in L1; however, we do not see any deregulation or enrichment of Stat motifs with castration in our scATAC studies. Furthermore, STAT chromatin recruitment has not been demonstrated in any of the recent studies, leaving us to wonder how JAK/STAT may be regulating treatment-induced plasticity.…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand, inhibitors of WNT/b-catenin (XAV-939), AKT (Capiversatib), HDAC (Panobinostat) and proteosome/NFkB (Bortezomib) all demonstrated an inhibitory effect or trend on prostate regeneration (Figure 6J), implicating these pathways in driving L1 generation and L1 regenerative activities. We also find JAK/STAT, which has received a lot of attention recently in relation to advanced PCa lineage plasticity [78][79][80] , to be one of the pathways deregulated in L1; however, we do not see any deregulation or enrichment of Stat motifs with castration in our scATAC studies. Furthermore, STAT chromatin recruitment has not been demonstrated in any of the recent studies, leaving us to wonder how JAK/STAT may be regulating treatment-induced plasticity.…”
Section: Discussioncontrasting
confidence: 61%
“…In term of metastases, Wang et al found that JAK2 and STAT3 can contribute to cancer cell proliferation and migration in colorectal cancer 28 . In term of treatment, JAK-STAT inflammatory signaling was enhanced in prostate cancer tumor cells which can lead to drug resistance 13 , 29 . JAK-STAT axis is a core signaling axis in a wide variety of t cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, TET2 and TET2-dependent 5hmC oxidation is known to offset the transcriptional signaling driven by AR, which impairs the progression of primary PCa and is correlated with better clinical outcomes 34 .On the other hand, TET2-medaited 5hmC transition is highly enriched in the establishment of stem-like and neuronal lineages during development and carcinogenesis of various cancers 43,44 and, consequently, associated with poor clinical outcomes. Interestingly, TET2 was also implicated in the induction of cytokine signaling in T-cell-mediated immune responses 50 , which was known to regulate PCa lineage plasticity 17,18,64 . Contrary to the conventional view of its tumor suppressor role in primary PCa, our findings revealed that TET2-driven epigenetic reprogramming is a powerful mechanism that promotes the transition of mCRPC cancer cells from an AR-driven luminal lineage to a TET2-driven lineage plastic state expressing EMT-like, stem-like and NE-like lineages, which then fail to respond to AR-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%